Centro de tecnificación para ciclistas (2021)
The research project aims at an architectural result; this presnts the argumentative considerations that demonstrate the importace of equipment in spots results and how these should respond to the specific qualities of thed discipline, taking this into account the creation of a spots technification center , which is an equipment specialized training for sport and its modalities, allowing its users to significantly improve athletic performance and therefore increase the sporting achievements of the country